PERANCANGAN WEB FRANCHISE PEMPEK DAN MOBILE MONITORING BERBASIS ANDROID - Suprapti, Fera; Wintolo, Hero; Honggowibowo, Anton Setiawan (Compiler, 2012)
Franchising is essentially a marketing concept in order to expand the network of one way that is as strong just a conventional marketing strategy in developing the business franchise is considered to have many adventages, especially regarding financing, human resources and management, unless the brand owner’s willingness to share it whithothers by member of the franchise to pay some money to get the ringht conoperation and sale of a product, as well as selecting a highly effective distribution channels tobring products to consumers.            Processing franchise by leveraging information and communication technology is expected to encourage performance improvement and management of a franchise making it easier and more efficient in monitoring the sales report.            Applications android based mobile monitoring can facilitate franchise agent to supervise the sale of goods to see report data residing on the mobile web server and the data displayed in bar graph form.Keyword:   Franchise,  Mobile Monitoring,  Android